2018
DOI: 10.21769/bioprotoc.3053
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear/Cytoplasmic Fractionation of Proteins from Caenorhabditis elegans

Abstract: C. elegans is widely used to investigate biological processes related to health and disease. To study protein localization, fluorescently-tagged proteins can be used in vivo or immunohistochemistry can be performed in whole worms. Here, we describe a technique to localize a protein of interest at a subcellular level in C. elegans lysates, which can give insight into the location, function and/or toxicity of proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Samples were prepared with Laemmli sample buffer with 0.1 mM DTT. Equal protein amounts within respective fractions were loaded 60 and assessed via SDS-PAGE on 9% gels or gradient gels. Proteins were transferred to PVDF membranes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Samples were prepared with Laemmli sample buffer with 0.1 mM DTT. Equal protein amounts within respective fractions were loaded 60 and assessed via SDS-PAGE on 9% gels or gradient gels. Proteins were transferred to PVDF membranes.…”
Section: Methodsmentioning
confidence: 99%
“…In this protocol, we loaded equal protein amounts for each respective fractions, and normalized the levels of the target proteins within respective fractions to a fraction marker (GAPDH and p84 for cytoplasmic and nuclear fractions, respectively), to cancel out the potential loading error [61][62][63] . This protocol is suited for comparing protein levels in the nuclear fraction before and after PDGF treatment but not designed to compare protein abundance between the cytoplasmic and nuclear fractions 60 .…”
Section: Methodsmentioning
confidence: 99%
“…Subcellular fractionation was performed as described in ref. 36 . Briefly, one-day-old animals grown at 20˚C were washed with M9 buffer until the supernatant was clear and then washed twice with 1 ml cold hypotonic buffer (15 mM HEPES KOH pH7.6, 10 mM KCl, 5 mM MgCl2, 0.1 mM EDTA, 350 mM sucrose).…”
Section: Cytoplasmic and Nuclear Fractionationmentioning
confidence: 99%
“…After homogenization, the cytoplasmic fraction was separated from the nuclei by centrifugation, and the nuclei were lysed in a hypotonic buffer to obtain nuclear extract. We subsequently checked the effectiveness of our subcellular fractionation through Western blot analyses of the cytoplasmic fraction and nuclear extract using αtubulin and histone H3 as marker proteins, respectively (17). Western results showed that α-tubulin mainly appeared in the cytoplasmic fraction and not in the nuclear fraction, whereas histone H3 was exclusively detected in the nuclear extract (Fig.…”
Section: Preparation Of C Elegans Nuclear Extractmentioning
confidence: 99%